Avaliação em educação física no ensino fundamental: relevância, característica e perspectiva de ajustamento sob o ponto de vista docente - Pereira, Leonardo Pavan (Universidade Federal de São Carlos, 2025)
It seems to be a consensus that the act of assessing is of fundamental importance to the pedagogical process. It is advocated that such practice should guide teaching actions in a way that helps teachers develop strategies to enhance student learning. However, although research on assessment processes in education has advanced in recent years, there is a notable need for expanding knowledge on this topic, especially in school Physical Education. In this sense, the study aims to investigate, from the perspective of Elementary School Physical Education teachers, the relevance, characteristics, and adjustment perspective of the assessment process systematized by a municipal education network. This is a qualitative, exploratory research involving 55 Physical Education teachers who teach in the Elementary School of the municipal network in question. The instrument used for data collection will be a semi-structured questionnaire containing 23 open and closed-ended questions administered through the Google Forms tool. The data analysis will be conducted in three distinct stages: 1. Data organization; 2. Data classification or categorization; and 3. Final analysis. The results revealed that 90.9% of the responding teachers believe in the applicability (usefulness) of the instrument, and for 94.5% of the teachers, the assessment spreadsheets are easy to understand and use. Furthermore, 85.5% of the teachers believe that the spreadsheets contribute to the credibility of grade and/or concept assignment in Elementary School Physical Education, and 87.3% are in favor of the systematization of the assessment process implemented by the municipality. 85.5% consider that the instrument favors an assessment process with a diagnostic and formative emphasis, and 63.6% of the teachers agree with maintaining the assessment instrument proposed by the municipality, though adjustments are needed for its effectiveness.
Assessment in physical education in elementary school: relevance, characteristics and adjustment perspectives from the teachers viewpoint
Keywords: Avaliação; Educação física escolar; Ensino fundamental; Assessment; School physical education; Elementary school; CIENCIAS HUMANAS::EDUCACAO::PLANEJAMENTO E AVALIACAO EDUCACIONAL